Strategic Choices For Stakeholders To Understand Asean Framework Agreement On Services (AFAS) As An Entry Mode Of Choice In Internationalization In Schedule Of Commitment (Soc): Evidence From The Services Industry - Herlitah, Herlitah; Swaramarinda, Darma Rika; Afrilliana, Nadia (PRAGMATIS, 2025)
In this services trade cooperation, each country will commit to open cooperation in the twelve service sectors with different levels of openness in each country and stated in the Schedule of Specific Commitment. The level of openness is divided into three levels, namely: fully opened without any restrictions, none which means it is opened with restrictions, and unbound which means it has not been opened. This will have an impact on the choice of entry mode that business actors will make, but until now in Indonesia it has not been utilized, especially with the results of bilateral, regional and multilateral trade cooperation negotiations. For this reason, understanding the entry mode will determine the choice of type of entry mode that will be carried out by business actors, the support or facilities that will be provided by the Government, and what activities the Association can carry out so that the restaurant internationalization process can run well. The method used in this research is descriptive analysis by understanding how to read the ASEAN Framework Agreement on Services (AFAS) cooperation in the restaurant service industry sector. For this reason, the author explains how to understand the existing regulations AFAS countries in ASEAN, as well as investment options that comply with destination country regulations.